In‐depth analysis of crocetin ester glycosides from dried/processed stigmas of Crocus sativus L. by HPLC‐ESI‐MSn (n = 2, 3). Issue 3 (15th January 2019) - Pittenauer, Ernst; Rados, Edita; Tsarbopoulos, Anthony; Allmaier, Günter
Abstract: Introduction: Saffron stigmas from Crocus sativus L. ( Iridaceae ) are used as a drug in folk medicine, as a food additive and as a dying agent for at least 3500 years. Despite this long‐term use the chemical composition of saffron seems still to be not fully known. Objective: An analytical strategy for detailed investigations of aqueous saffron extract is developed based on reverse‐phase high‐performance liquid chromatography electrospray ionisation (HPLC‐ESI) multistage mass spectrometry (MS n ) for crocins. Methods: Commercially available stigmas are analysed by reverse‐phase HPLC in combination with ESI/three‐dimensional (3D)‐ion trap mass spectrometry (MS) and MS n ( n  = 2 and 3). Sodium chloride is added to the analyte solution ready for injection to promote abundant [M + Na] + adduct ions of crocins, being ideal precursor ions for low‐energy collision‐induced dissociation (CID)‐MS 2/3 . Results: This strategy allows the detailed structural elucidation of known as well as previously unknown crocin derivatives (molecular mass of the aglycon, oligosaccharide chain length and linkage determination). The two isomeric trisaccharide substituents neapolitanose and gentiotriose are distinguished based on linkage‐specific cross‐ring cleavage for the first time. Furthermore, crocins containing up to six hexose units are also observed. Five novel crocin ester glycosides shifted by a mass difference of −40 Da indicate the presence of the here newly described C17 ‐aglycon, termed norcrocetin (crocetin = C20 ). Conclusions: These findings indicate the action of at least two different carotenoid cleavage dioxygenases (CCD2 and tentatively CCD4) during biosynthesis of this new bis‐apocarotenoid aglycon (norcrocetin) and the existence of even higher glycosylated crocin derivatives at trace level. Abstract : An analytical strategy for detailed structural investigations of aqueous saffron extract from Crocus sativus L. ( Iridaceae ) is developed based on reverse‐phase high performance liquid chromatography electrospray ionisation multistage mass spectrometry (MS n, n  = 2 and 3) for crocins. This approach allows the determination of the molecular mass of the aglycon and linkage determination of the oligosaccharide substituents. Crocins with at least up to six hexose units and even with a new C17 ‐aglycon termed norcrocetin (crocetin: C20, Δ m  = 40 Da) are described for the first time.